Causes of Attrition of B-school Faculty Members at Bangalore, India: An Empirical Study - Roopa Temkar (Progress in Language, Literature and Education Research Vol. 9, 2024)
In the scenario of increasing demand for management education, the number of B-schools has mushroomed, but unfortunately, required quality is not maintained, which has led to a lack of job opportunities and high expectations from employers. Knowing the dearth of quality education and increased rate of faculty member attrition in the last few years with the increase in the number of B-schools in Bangalore, the management has the challenge of conjoining its goals with the faculty aspirations, in order to successfully overcome the problem of high attrition and attracting and retaining the best performers. To solve the problem of attrition of faculty members, retention of faculty members is inevitable for the success of B-schools. In order to ensure quality education, there is a need for strategies for recruiting and retaining talented faculty members. The researcher has used 12 variables/dimensions to address the research questions. For the study, the sample size is 455 (407 faculty members from VTU and BU affiliated B-schools and 48 management members from the same VTU and BU affiliated B-schools). The proposed study is a descriptive qualitative research. The investigation is carried out at B-schools affiliated with VTU and BU in the city of Bangalore. The data collected is tabulated and analyzed using the SPSS 20.0 version, correlation analysis, group statistics, and ANOVA with more emphasis on factor analysis, percentage and ranking methods. To know in detail the general causes of attrition of faculty members in B-schools and its impact on individuals and organizations has also been studied and presented. The important findings depicted that the majority of the management respondents agree that the attrition is less. But the majority of the faculty members, have agreed that, they joined the institution because of vacant positions, and this has recorded the highest percentage against the joining of faculty members because of the increase in the intake of students. An interaction with a few ex-faculty members, based on their exit interviews in a few institutions revealed that there is a gap between the responses of management and faculty members. The need of the hour for every B-school is, motivating and retaining such faculty members and to think and adopt a vigorous human resource policy which would really give confidence about the institute in their minds. Faculty members are keen on such strategic career moves which assure employment and satisfaction towards job security.